Electrospun Biopolyesters: Hydrophobic Scaffolds with Favorable Biological Response - Azari, Pedram; Hosseini, Samira; Pinguan Murphy, Belinda; O. Martinez-Chapa, Sergio (Journal of Public Health International, 2018)
This article reviews electrospun biopolyester scaffolds, focusing on surface hydrophobicity, cell response, and applications in tissue engineering.
Keywords: electrospun biopolyester scaffolds; tissue engineering